Cementless knee arthroplasty - Ponziani, Lorenzo; Di Caprio, Francesco; Meringolo, Renato (Acta Biomedica Atenei Parmensis, 2017)
Total knee replacement is a common treatment for advanced knee osteoarthritis. The most common and widespread method is cemented arthroplasty. As in the prosthetic hip a gradual transition from cemented to uncemented fixation techniques occurred over time, increasing interest is growing also around cementless knee fixation, with the theoretical advantages of preserving the bone stock and obtaining a biological fixation avoiding cement fragmentation. On the basis of the actual knowledge, the uncemented knee prosthesis represents an interesting alternative especially for the patient under 65 years of age, with viable bone quality, in which a biological bone-prosthesis fixation is desirable, while avoiding the drawbacks of cement fragmentation and of the possible future revision of a cemented implant. However the weak link remains the tibial fixation, so that technical tips are important to avoid micromovements with subsequent lack of osteointegration. In our experience, gap balancing, mobile bearings and no haemostatic tourniquet well combine with this kind of implant.